Hidden options and player pushback: rhetoric of Mass Effect 2 - Robson-May, Rebekah, author; Sloane, Sarah, advisor; Lamanna, Carrie, committee member; Cross, Jennifer E., committee member (Colorado State University. Libraries, 2011)
This thesis is an exploration of gender construction within the digital gaming subculture of the United States in the early 21st century. Using the 2010 game Mass Effect 2 as an organizing theme and central focus, the thesis examines how gender is constructed within this single-player role-playing game; how marketing materials reveal expectations about audience for this game and two other single-player role-playing games released in 2010 (Fable III and Final Fantasy XIII); and how online communities related to games, particularly to Mass Effect 2, both reinforce normative assumptions and attitudes about gender for players of digital games and characters within the games, and how they offer opportunities for the subversion and disruption of these normative models. Theories from Judith Butler and from Candace West and Don Zimmerman provide the primary basis for exploring gender construction. To examine the effects of digital games on literacy and learning, James Paul Gee's work is used extensively. Additional discussion utilizes online fan and gamer posts. Insights about games, their marketing, and the broader community are drawn from a number of perspectives, including autoethnography, visual rhetoric, the principles of interpreting visual art, and a study of theatrical costume design.
Keywords: video games; online community; single-player role-playing games; rhetoric; gender construction; marketing